2020
DOI: 10.34067/kid.0003912020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Polycystic Kidney Disease in Rodents: Comparison of Robotic 3D Ultrasound and Magnetic Resonance Imaging

Abstract: Polycystic kidney disease (PKD) is an inherited disorder characterized by renal cyst formation and enlargement of the kidney. PKD severity can be staged noninvasively by measuring total kidney volume (TKV), a promising biomarker that has recently received regulatory qualification. In preclinical mouse models, where the disease is studied and potential therapeutics are evaluated, the most popular noninvasive method of measuring TKV is magnetic resonance imaging (MRI). Although MRI provides excellent 3D resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Importantly, the robotic US system fits on a table or bench and is more cost-efficient. Finally, prior work demonstrated that robotic US could provide comparable measurement data to more expensive modalities, such as MRI 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the robotic US system fits on a table or bench and is more cost-efficient. Finally, prior work demonstrated that robotic US could provide comparable measurement data to more expensive modalities, such as MRI 3 .…”
Section: Discussionmentioning
confidence: 99%